2019
DOI: 10.3390/ijerph16050879
|View full text |Cite
|
Sign up to set email alerts
|

Relative Risk Perceptions between Snus and Cigarettes in a Snus-Prevalent Society—An Observational Study over a 16 Year Period

Abstract: Background: Most studies on perceived risks of smokeless tobacco products (SLT) have been conducted in the U.S., and the vast majority conclude that perceptions of the relative harmfulness of SLT versus cigarettes in the population are inconsistent with epidemiologically-based risk estimates, and typically conflated to that of cigarettes. We tested whether such inaccuracies also existed in Norway, where SLT-products are less toxic (Swedish snus) and SLT use is more prevalent than in the U.S. Methods: Over a 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 55 publications
2
16
0
Order By: Relevance
“…In a study using survey data from Norwegians aged 16-79 in the years 2003-2018, the harmfulness of daily snus use was rated only somewhat lower than daily smoking. These perceptions did not appear to have changed during the last 16 years [3]. As for specific diseases, another study found that the majority of Norwegian smokers estimated that the risk for cardiovascular disease, oral and stomach cancer was equal or higher for snus users [4].…”
Section: Introductionmentioning
confidence: 99%
“…In a study using survey data from Norwegians aged 16-79 in the years 2003-2018, the harmfulness of daily snus use was rated only somewhat lower than daily smoking. These perceptions did not appear to have changed during the last 16 years [3]. As for specific diseases, another study found that the majority of Norwegian smokers estimated that the risk for cardiovascular disease, oral and stomach cancer was equal or higher for snus users [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, experiences of other tobacco users may be different [ 36 ]. For example, snus use may be less stigmatizing [ 36 , 45 ] as it is not perceived as harmful as smoking [ 46 ] and does not expose others to second-hand smoke [ 45 ]. Perceived tobacco-related stigma may also be higher in Sweden compared to other settings where the prevalence of tobacco use is higher and more normalized.…”
Section: Discussionmentioning
confidence: 99%
“…Anyway, if a causal association between snus use and subsequent smoking really exists, ecological trend data indicates that this association must have been dwarfed by other factors protecting against smoking uptake. Because at the population level, an inverse correlation between snus use and smoking has been observed among young adults in Norway [ 10 ], and recently also between vaping and smoking in the USA [ 55 ] and in New Zealand [ 56 ]. Thus, lending support to the "diversion theory" hypothesizing that snus/e-cigarettes might deter cigarette smoking by diverting "high-risk" individuals to snus/e-cigarettes from combustible cigarettes.…”
Section: Discussionmentioning
confidence: 99%
“…Among young adults (16-24 years), this shift took place around 2006 among men and around 2011 among women [9]. The inverse correlation between the trends in smoking and snus use in the Norwegian population after 2000 has been described in several publications [10][11][12].…”
Section: Introductionmentioning
confidence: 99%